INTANGIBLE CULTURAL HERITAGE AND THEIR INFLUENCE ON FINANCIAL RESULTS IN RURAL TOURISM - Starčević, Krešimir; Vojinović, Željko; Glavaš, Jerko (Economics of Agriculture, 2022)
Many scientists and native stakeholders are increasingly pointing to the importance of connection between cultural heritage and tourism, and influence of that connection on the financial results of entrepreneurs in rural tourism. Therefore, the importance of cultural heritage and especially intangible cultural heritage is being discussed. In the continuation, the status of connection between intangible cultural heritage and rural tourism is analyzed. The paper further points to the need for planned and organized, stronger content linking of rural tourism and intangible cultural heritage, that should influence financial results of the entrepreneurs in rural tourism. An example from the Croatia is given which is using intangible cultural heritage (traditional music and dance) in (rural) tourism offering. The link between this connection and financial results of the company is analyzed. The conclusion provides recommendations for better connection of the intangible cultural heritage and the rural tourism, ensuring the better financial results.